Influence of carbon tetrachloride on nuclear-magnetic relaxation characteristics of sunflower lecithins - E. P. Viktorova; O. S. Agafonov; S. M. Prudnikov; T. A. Shahray; I. I. Ukrayintseva (Новые технологии, 2018)
The article presents the results of the research on the effect of carbon tetrachloride on the change in the nuclear magnetic relaxation characteristics of protons contained in sunflower lecithins